Aided regeneration system of aged asphalt binder based on microcapsule technology. (20th March 2019) - Sun, Daquan; Li, Bin; Tian, Yang; Lu, Tong; Zhu, Xingyi; Sun, Guoqiang; Gilabert, Francisco A.
Highlights: The volume ratio of core materials (rejuvenator) to microcapsule reached 95%. Microcapsules containing rejuvenator can survive during mixing and be broken during loading. Microcapsules restore rheological properties of aged asphalt binder and prolong its fatigue life. The healing efficiency of aged asphalt binder is proportional to the content of microcapsules. Abstract: The microencapsulated rejuvenator within asphalt is a promising alternative approach to prolong the service life of asphalt pavement. The aim of this paper is to investigate the aided regeneration system of aged asphalt binder based on microcapsule technology. The microcapsules containing rejuvenator were fabricated by in-situ polymerization method, and the capsule shell was made of melamine-urea-formaldehyde (MUF) resin. Firstly, the micro-morphology of microcapsules was characterized by scanning electron microscope (SEM). It could be found that the volume ratio of the core materials (rejuvenator) to microcapsule reached to 95%. Further, the time sweep fatigue test together with fluorescence microscope (FM) was employed to study the rupture behavior of microcapsules in aged asphalt binder before and after loading. The test results indicated that the microcapsules had sufficient thermal stability and strength to suffer from mechanical agitation at a high temperature. In addition, the rejuvenator released from microcapsules partially restored complex shear modulus and phase angle of aged asphalt binder thus extended its fatigue life. Finally, the fatigue-rest-fatigue test using dynamic shear rheometer (DSR) was conducted to study the effect of microcapsules on the fatigue resistance and healing capacity of aged asphalt binder. The test results showed that the fatigue resistance of aged asphalt binder was enhanced by microcapsules containing rejuvenator and the fatigue life of aged asphalt binder with 1 wt% microcapsules was 45.68% higher than that of non-aged neat asphalt binder. Moreover, the microcapsules could improve the healing capacity of aged asphalt binder, and its healing efficiency was proportional to the content of microcapsules.